Kajian Elemen-Elemen Visual Dalam Penceritaan Kisah Penciptaan Dunia Menurut Agama Katolik Yang Menarik Untuk Anak Usia 6-11 Tahun - Agatha Maisie Tjandra (ULTIMART Jurnal Komunikasi Visual, 2013)
In Catholic Religion, Bible is the most important element to convey people about Jesus teachings. But, there problem is, Bible can’t be easily read by children. This problem happens because Bible is presented by words only. In the other hand, most of kids love to see picture than words because it is more inter-esting. The purpose of this paper is to know what kind of book elements that at-tract kids, so they feel interested to read Bible. The metodology used on this re-search is descriptive quantitative research. Key words : Element, Bible, Pop-Up